Abrindo a caixa-preta da divulgação ambiental em diferentes modelos de capitalismo - Pinheiro, Alan Bandeira (2021)
Although the effect of institutional characteristics of countries on corporate social responsibility disclosure has been extensively examined in the literature, it is still unclear how environmental disclosure practices vary according to the type of capitalism a country adopts. The aim of this research is to investigate the effect of capitalism characteristics on firms' engagement in environmental disclosure. To achieve this aim, the research analyzed, the research analyzed, for 10 years (2009-2018), a sample of 6257 companies, headquartered in 55 countries and in 8 typologies of capitalism: highly coordinated economy, coordinated market economies, market economies liberal, peripheral European economies, advanced emerging economies, advanced city economies, Arab oil-based economies, and emerging economies. The dependent variable is the companies' environmental disclosure, measured through the construction of an environmental performance index, which assesses 25 indicators on recycling, energy consumption, biodiversity, atmospheric emissions, effluents and water, waste, spills, and environmental impacts. The independent variables are the spheres of capitalism, measured through seven indicators: cooperation between employees and employers, index of economic freedom, local competition between industries, density of unions, human development index, quality of the governance and protection environment to minority shareholders. The results show that in countries with greater economic freedom, companies disclose less environmental information. Greater local competitiveness among companies favors the engagement of companies in environmental disclosure. Furthermore, in countries with a higher human development index and greater protection for minority shareholders, companies have greater environmental responsibility. The findings also reveal that a better institutional governance environment is a determining factor for firms' engagement in environmental disclosure. Additionally, it was found that a better financial performance of the firm and certain institutional factors such as the legal and communication system that the country follows can also influence environmental disclosure. Therefore, it is proven that the environmental behavior of firms is shaped by the characteristics of capitalism in the country where they operate. These findings have important academic, managerial, and governmental implications, presenting new directions for research on corporate social responsibility.